trans-Di-mu-bromo-bis[bromo(triethylphosphine-kappaP)platinum(II)]. - Cornet, S; Dillon, K; Goeta, A; Thompson, A (2005)
The title compound, [Pt2Br4(C6H15P)2], is a centrosymmetric dinuclear platinum(II) complex consisting of two square-planar platinum centres connected by two bridging Br atoms.